Medicinal Use of Cannabis: History and Current Status - Harold Kalant (Pain Research and Management)
OBJECTIVE: To provide an overview of the history and pharmacology of cannabis in relation to current scientific knowledge concerning actual and potential therapeutic uses of cannabis preparations and pure cannabinoids.